Precipitation Behaviour of Low Carbon Microalloyed Steel. Issue 1 (March 2021) - Singh, Harikesh; Singh, Ashish Kumar; Hyderi, Zakir Ali; Banerjee, M.K.
Abstract: In this paper precipitation behaviour of low carbon micro alloyed steel is seen by various heat treatment cycles at different temperature ranges. Precipitation occurs during the ageing cycles and as we can conclude from harness graph and microstructural study that precipitation of alloys like NbC, SiC, CrC, NiC, VC, MoC, BC precipitates on higher temperatures, therefore hardness tends to increase at some range of high temperature ageing. After their precipitation occurs there got a saturation in the system and again hardness tends to fall. Although the hardness result of all the samples do not show very significant difference, but as a whole the test shows rise, saturation and fall in hardness values which is due to various precipitation temperatures of various alloying elements involved.